Protein utilisation and intermediary metabolism of Senegalese sole (Solea senegalensis) as a function of protein:lipid ratio - Borges, Pedro (2018)
Previous experiments with Senegalese sole (Solea senegalensis) have demonstrated that dietary lipid levels above 8% impaired growth and did not promote protein retention. We hypothesised that this low ability to use high-lipid diets may depend on the dietary protein level. In the present study, a 2 x 2 factorial design was applied where two dietary lipid (4-17% DM) and two dietary protein (below and above the requirement levels, 48 and 54% DM) levels were tested in juveniles for 114 d. Growth performance was not improved by the increase in dietary fat, irrespectively of the dietary protein levels. Protein retention was similar among the diets, although fish fed the diets with high lipid content resulted in significantly lower protein gain. Among the enzymes involved in amino acid catabolism, only aspartate aminotransferase activity in the liver was affected by the dietary lipid levels, being stimulated in fish fed high-lipid diets. Moreover, phosphofructokinase 1 activity was significantly elevated in the muscle of Senegalese sole fed 4% lipid diets, suggesting enhanced glycolysis in the muscle when the dietary lipid supply was limited and dietary starch increased. The results confirmed that high-lipid diets do not enhance growth, and data from the selected enzymes support the assumption that lipids are not efficiently used for energy production and protein sparing, even when dietary protein is below the protein requirement of the species. Furthermore, data suggest a significant role of glucose as the energy source in Senegalese sole.